Students' Reflective Journals and Creative Writing in EFL - Haya Abdul Rahman Abu Hussein; Deena Abdul Hameed Al Jamal; Imad Sadi (Universal Journal of Educational Research, 2023)
This study aimed at investigating the effectiveness of online reflective journals on Birzeit University students’ creative writing. The participants of the study were sixty first-year university students. They were chosen randomly from Birzeit University in the second semester of the academic year 2019/2020. The study followed the quasi-experimental design. The participants were divided into two groups: an experimental group (n=30) and a control group (n=30). To carry out the study, the researcher taught her students how to write reflective journals, and she established a closed group on Messenger for her students to write their online reflective journals and share them on the group frequently each time on a different topic. The data about the students’ creative writing skills were collected using a creative writing pre/post-test designed by the researcher. The data were analyzed using appropriate quantitative analyses. The results of the study showed that the proposed instructional strategy was effective in improving students' creative writing skills. The results proved that the strategy of online reflective journals has positively affected the components of creative writing (originality, flexibility, fluency, and elaboration).